SOCIALLY DIVIDED: AFFORDANCES, GENDER, AND RACE IN FACEBOOK - Cirucci, Angela (AoIR Selected Papers of Internet Research, 2015)
This study investigates created, non-neutral affordances granted by social networking sites and their implications for perceptions of marginalized communities. I employ Facebook as a case study and speak with emerging adults to comprehend how socially marginalized groups are represented through Facebook’s affordances. In particular, I consider: How familiar are users with Facebook’s affordances?; How are issues of gender and race represented through Facebook?; and How do users conceive of gender and race?